Vibro-tactile Feedback for Dial Interaction using an Everyday Object in Augmented Reality - Greenslade, Mac; Clark, Adrian; Chen, Zhe; Lukosch, Stephan (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
Interaction using everyday objects offer a compelling alternative to gesture and dedicated controller interaction in augmented real-ity. However, unlike dedicated controllers, everyday objects cannot provide active haptic feedback. To explore active feedback with everyday objects, a within-subjects study was conducted with n = 28 participants, using a flowerpot enhanced with vibro-tactile feedback to perform dial interactions and comparing four conditions based on the inclusion and exclusion of audio and haptic feedback. No significant differences between conditions were found for task com-pletion time or accuracy, however measurements of immersion and user preference were higher for the conditions that included haptic feedback.